TOURISM AND ECONOMIC DEVELOPMENT IN SRINAGAR: A CASE STUDY OF THE KASHMIR VALLEY - Dr. Shabir Ahmad Lone,; Dr. E. Ravi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Development is generally seen as a continuous process that promotes economic growth, social improvement, and positive changes in society. Its main goal is to improve the quality of life of people by creating income and employment opportunities while also protecting environmental resources. In this regard, tourism has become one of the largest and fastest-growing industries in the world, contributing greatly to both national and regional economies. In Jammu and Kashmir, tourism is an important and multi-dimensional sector that provides various employment opportunities in areas such as hospitality, travel services, guiding, transportation, and other related activities. The region’s rich culture and beautiful natural landscapes attract many visitors and help boost economic activity, contributing nearly 6.99 percent to the region’s GDP. Due to the mountainous terrain, large-scale industrial development is limited, so tourism acts as a key economic alternative. This is especially true in Srinagar District, which has great tourism potential and many business opportunities. However, the tourism sector has often been negatively affected by periods of instability and violence in the region. This study aims to examine the role of tourism in fostering economic growth and development in Jammu and Kashmir, with special reference to Srinagar, while also identifying key challenges. The research is qualitative in nature, relying on primary and secondary data, and employs a documentary and analytical approach using thematic tools to ensure objective conclusions.